Mason & Dixon - Pynchon, Thomas (Henry Holt and Company, 1997)
The lives of two 18th century British astronomers who surveyed the boundary which settled a dispute between Maryland and Pennsylvania, and was later extended to become the boundary between free and slave states, the Mason-Dixon line. The novel describes their work in Africa and America, and traces their relationship. By the author of Vineland.